Thermoregulation and heat exchange in ospreys (Pandion haliaetus). (February 2021) - Rogalla, Svana; Shawkey, Matthew D.; Vanthournout, Bram; D'Alba, Liliana
Abstract: The osprey ( Pandion haliaetus ) is a cosmopolitan and long-distant migrant, found at all thermal extremes ranging from polar to tropical climates. Since ospreys may have an unusually flexible thermal physiology due to their migration over, and use of, a wide range of habitats, they represent an interesting study system to explore thermoregulatory adaptations in a raptor. In this study, we investigated the efficiency of heat exchange between body and environment in ospreys using micro-computed tomography (μ-CT), infrared thermography and behavioral observations. μ-CT revealed that the osprey bill has its largest potential for heat exchange at the proximal bill region, where arteries are situated most closely under the surface. However, thermal images of 10 juvenile ospreys showed that the bill contributes to only 0.3% of the bird's total heat exchange. The long legs and protruding claws played a more prominent role as heat dissipation areas with a contribution of 6% and 7%, respectively. Operative thresholds, i.e. the ambient temperature below which heat is lost, were high (>38.5 °C) in these body parts. However, we found no indication of active regulation of heat exchange. Instead we observed multiple behavioral adaptations starting at relatively low ambient temperatures. At 26.3 °C ospreys had a 50% probability of showing panting behavior and above 27.9 °C they additionally spread their wings to enable heat dissipation from the less insulated ventral side. The thermal images revealed that at an ambient temperature of 32.1 °C ospreys had a 50% probability of developing a ≥2 °C and up to 7.5 °C colder stripe on the head, which was likely caused by cutaneous evaporation. Our observations suggest that ospreys more strongly rely on behavioral mechanisms than on active thermal windows to cope with heat stress. This study not only improves our understanding of the role of different body parts in ospreys' total heat exchange with the environment but further provides an insight about additional adaptations of this raptor to cope with heat stress. Highlights: Legs, claws and bill in ospreys function as heat dissipation areas. We found no indications for an active control of heat exchange through these areas. Behavioral adaptations to cope with heat stress included panting and wing spreading. With thermography we visualized cutaneous evaporation as a cooling mechanism.